VISUAL INTENSITY IN THE FENOMENOLOGICAL ANALYSIS DISCUSSIONS - Ільїна, Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article investigates the problem of "visual culture" in the context of phenomenological discourses E. Husserl, M. Merlot-Ponti, J.-P. Sartre It is shown the "output" of phenomenological consciousness in the world of human life, in the field of the experience of corporeality, which allows us to get a real vision of reality. The analysis of the problem of "sight" as an understanding of the spatio-temporal essence of the objective world and the place in it of its own "I" in relation to "Other" is carried out.